ANALISIS EFEKTIVITAS PENGELOLAAN AIR LIMBAH RUMAH SAKIT BHAYANGKARA KUPANG - Mengge, Reinaldy Endhrico; Suratma, Susana Maria; Tallo, Amandus Jong (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
Hospitals are significant producers of liquid waste that have the potential to pollute the environment if not properly managed. Hospital wastewater contains organic and inorganic substances, pathogenic microorganisms, and hazardous chemicals. This study aims to evaluate the effectiveness of the Wastewater Treatment Plant (WWTP) at Bhayangkara Hospital Kupang based on chemical and microbiological parameters, including pH, temperature, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), oil and grease, and total coliform. The study uses a descriptive qualitative method with secondary data analysis from laboratory results. The results show that all parameters are below the threshold of environmental quality standards set by the Ministry of Environment Regulation No. 5 of 2014, with values for: pH (7.255), temperature (28°C), BOD (38.7 mg/L), COD (76 mg/L), TSS (0.06 mg/L), TDS (363 mg/L), oil and grease (0.016 mg/L), and total coliform (438/100 mL). These results indicate that the WWTP at Bhayangkara Hospital Kupang operates effectively in treating wastewater, making the discharged wastewater suitable for disposal into the environment and in compliance with the established quality standards.